The Particle Size and Thermal Properties of Flour from three Plantain (Musa Paradisiaca) Cultivars Grown in Nigeria - Barine, Kiin-Kabari David; Victor, Njoku (Journal of Food Technology Research, 2016)
Flour from three plantain cultivars (Agbagba, Cadaba and French horn) commonly grown in Nigeria were investigated for their particle size, bulk density and thermal properties. The results showed that Agbagba cultivar had the least particle size (10.04%) at 125µm sieve size and significantly increased to 29.45% at 180µm sieve size. Cadaba and French horn plantain cultivars showed a particle size of 56.54% and 36.20% at 125µm sieve size, respectively and decreased significantly with increase in sieve sizes. The bulk density ranged from 28.62% to 30.50% and showed no significant differences between the cultivars. The moisture content ranged from 7.65% (French horn) to 8.7% for (Cadaba) and showed no significant difference (p > 0.05). Also, there were no significant differences (p > 0.05) observed in specific heat capacity, thermal conductivity and thermal diffusivity between the cultivars studied. The data thus obtained showed that chemical composition of the cultivars may influence thermal properties and this will serve as a useful engineering tool for the design and development of sieves and dryers for plantain flour.